Effect of ultra-disperse powder оf zirconate-titanate lead on morphological and functional status of kidney studied experimentally - N. M. Shevtsova; V. V. Novitsky; Ye. A. Stepovaya; S. V. Nizkodubova (Бюллетень сибирской медицины, 2007)
Rat experiments revealed that daily inhalation of ultra-disperse powder (UDP) оf zirconate-titanate lead in a dose of 15 mg/m3 re-sult in increased contents of single element of UPD in kidneys and cause changes of morphological and functional status of the or-gan. According to accumulation degree in kidneys, the studied chemical elements are situated in the following sequence: Pb > Ti > Cr > Mn. The presented results are indicative of moderately expressed toxic effect of UDP of circonate-titanate lead on morphological and functional status of rat's kidney, been subjected to its inhalation influence.